CHARACTERISTICS OF STORIES AND IMAGES IN THE QURAN - Putri, Endrika Widdia (UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This research explores the characteristics of stories and parables in the Quran. This research is qualitative research using exploratory and analytical methods. The results found regarding the characteristics of the story in the Quran, namely; arranged in themes, has a purpose and is substantially religious; not arranged sequentially and not at length; several stories are told repeatedly which vary. While the characteristics of parables in the Quran, namely; explanation of abstract meaning; the parallels between the conditions of the parable referred to and their equivalents; a balance between the parable and the analogous state.